THE EFFECT OF CONCEPT MAPPING STRATEGY ON STUDENTS' READING COMPREHENSION AT MA ARRASYID TEMBILAHAN - Syafrizal, Syafrizal (Fakultas Keguruan dan Ilmu Pendidikan, Program Studi Pendidikan Bahasa Inggris, 2018)
This study is aimed at finding out the effect of concept mapping strategy on the students’ reading comprehension. The study was done through quasi-experimental design which involved pre-test and post-test procedures. There was a try out before administering the tests. Then,the pre-test was administered before giving treatments and the post-test was administered after the treatments. The data collection techniques were tests. The population consisted of 119 students. A cluster sampling technique was used to take them as samples. The samples were divided into two groups; experimental group and control group. Then, the data were analyzed using t-test and paired sample t-test methods to find out whether there was significant difference between the experimental group taught by using concept mapping strategy as the treatment and the control group taught conventionally. The results of the research shows that the significant probabilities were higher than 0.05 (>0.05) ) in both paired sample t-test and independent sample t-test. It meant that there was significant difference on the students’ reading comprehension in the pre-test and in the post-test of the classes. There was also a significant difference on their reading comprehension before and after treatments in the experimental class. The value of eta square was 0.68 for their reading comprehension. In sum up, the the application of concept mapping gives positive effect toward the students’ reading comprehension.